Forming of High School Students’ Preparedness to Professional Education at Higher Educational Establishments - Sadovets’, Olesa (Pedagogical Discourse, 2012)
An urgent problem of forming an adequate level of high school students’ preparedness to entering and successful studying at higher education establishments has been highlighted in the article. Possible measures on the level of national and local education authorities as well as school administrations concerning the improvement of such preparedness level have been analyzed. The role of curricula system in this process has been defined; steps concerning their improvement have been outlined; algorithm of composing curricula for high school students has been presented. Positive foreign experience of filling in the achievements gaps of high school students has been analyzed.